Energy Management Systems Using Smart Grids: An Exhaustive Parametric Comprehensive Analysis of Existing Trends, Significance, Opportunities, and Challenges. (21st October 2022) - Khan, Nitasha; Shahid, Zeeshan; Alam, Muhammad Mansoor; Bakar Sajak, Aznida Abu; Mazliham, M. S.; Khan, Talha Ahmed; Ali Rizvi, Syed Safdar
Abstract : The integration of widely fluctuating distributed generation (such as photovoltaic panels, wind power, electric vehicles, and energy storage systems) puts the stability of power technologies and distribution structures in jeopardy. However, the fundamental reason is that the electrical supply and demand ratio may not be balanced. An excess or scarcity of electricity in the production or consumption of energy can disrupt the system and cause serious difficulties such as voltage drops/rises and, in extreme cases, power outages. Energy management systems can efficiently increase the balance between supply and demand while reducing peak load during unscheduled periods. The energy management system can handle distributing or exchanging energy among the many energy resources available and economically supplying loads in a stable, safe, and effective manner under all power grid operating situations. This article examines the energy control system's structure, goals, benefits, and challenges through an in-depth investigation of the various stakeholders and participants involved in this system. This review provides a detailed essential analysis of the operation of several programs used inside the power management system, such as demand response, demand management, and energy quality management. It also includes a summary of the smart grid's functionalities, features, and related techniques and has discovered research gaps, challenges, and issues. Furthermore, in this article, the authors review the literature on the enabling technologies of smart grid and investigate the energy management system, which is among one of the major emerging technologies and quantifications of the various uncertainty techniques. In this paper, the authors also discussed the comprehensive review of researchers' efforts and contributions to the smart energy management system in the smart grid. It also compares and evaluates the key optimization approaches utilized to achieve the remarkable aims of energy management structures while also fulfilling a variety of constraints. This comprehensive review will be very beneficial for the new researchers, and it would be a great contribution to the research community.